Care of HIV-positive women aged 50 and over – can we do better?. (March 2014) - Samuel, MI; Welch, J; Tenant-Flowers, M; Poulton, M; Campbell, L; Taylor, C
A sample of 123 HIV-positive women aged 50 years and over showed high rates of late diagnosis with CD4 count <350 (71%), significant co-morbidities (90%), high rates of premature menopause (6.8%) and early menopause (6.8%) and cervical cytological abnormalities (47%). Specific interventions to improve care in this group should include yearly cervical cytology, early counselling with regard to reproductive options, menopause management and screening for sexually transmitted infections (STIs).